Solvabilitas sebagai Cermin Nilai pada Perusahaan Properti dan Real Estate yang Terdaftar di BEI - Fatimah, Siti; Anisaul Hasanah; Bustanul Ulum (CV. ULIL ALBAB CORP, 2025)
This study investigates the effect of solvability on firm value in the property and real estate sector listed on the Indonesia Stock Exchange for the period 2019–2023. The research is grounded in agency theory and signaling theory, emphasizing the importance of financial risk management in influencing market perception. Using a quantitative associative approach with purposive sampling of 50 companies, solvability is measured by Debt to Equity Ratio (DER) and firm value by Tobin’s Q. The results indicate that solvability has a negative and insignificant effect on firm value, suggesting that high leverage may reduce investor confidence. The study highlights the need for prudent debt management to maintain financial stability and firm valuation.